AI-Enhanced Teacher Education and EFL Pre-Service Teachers’ Professional Identity: A Quasi-Experimental Study - Zhu, Mian; Hussin, Supyan; Hashim, Harwati (Forum for Linguistic Studies, 2025)
Professional identity development during pre-service teacher education has emerged as a critical factor influencing teaching effectiveness, career satisfaction, and teacher retention. For English teachers, this process is further shaped by their language learning and teaching context. In countries such as China, where English is taught as a foreign language (EFL), pre-service teachers’ professional identity formation involves not only pedagogical development but also the cultivation of language-related self-efficacy and cultural positioning within a non-English-speaking environment. This dual challenge distinguishes EFL pre-service teachers from their counterparts in ESL or native English-speaking contexts, where language proficiency is less of a concern. Concurrently, the rapid integration of artificial intelligence (AI) technologies in education presents both opportunities and challenges for teacher preparation programs worldwide. Although AI is increasingly used to support lesson planning, assessment, and reflection, empirical research examining its impact on EFL pre-service teachers’ professional identity remains scarce. Understanding how AI integration interacts with the unique challenges of EFL contexts is essential for designing effective and context-sensitive teacher education programs. This study employs a single-group quasi-experimental design to explore associations between AI-enhanced teacher education and professional identity development, acknowledging that such exploratory research provides preliminary evidence necessary for informing future controlled experimental studies. Highlights: This study examines the impact of an AI-enhanced teacher education program on EFL pre-service teachers’ professional identity in China. Findings reveal significant improvements in competence-related dimensions, especially self-efficacy. Results suggest that AI tools can act as scaffolds that strengthen pre-service teachers’ professional identity in authentic teaching contexts. The study highlights both the potential and limitations of AI integration, underscoring the need for more rigorous controlled research.